Lack of Restoration in Vivo by K+-Channel Modulators of Jejunal Fluid Absorption after Heat Stable Escherichia coli Enterotoxin (STa) Challenge - M. L. Lucas; L. C. Gilligan; C. C. Whitelaw; P. J. Wynne; J. D. Morrison (Journal of Tropical Medicine)
Enhanced potassium ion permeability at the enterocyte basolateral membrane is assumed to facilitate sustained chloride ion and fluid secretion into the intestinal lumen during episodes of secretory diarrhoeal disease. To examine this concept in vivo, two potassium ion channel blockers and a channel opener were coperfused with E. coli heat stable STa enterotoxin to determine whether such compounds improved or worsened the inhibited fluid absorption. In the STa (80 ng/mL) challenged jejunal loop, the fluid absorption rate of 28.6 ± 5.8 (14) μL/cm/hr was significantly below (P<.001) the normal rate of 98.8 ± 6.2 (17) μL/cm/hr. Intraluminal (300 uM) glibenclamide added to STa perfused loops failed to improve the inhibited fluid absorption rate, which was 7.4 ± 3.2 (6) μL/cm/hr on coperfusion with STa. Similarly, on coperfusion with 30 uM clotrimazole, the fluid absorption rate with STa present remained inhibited at 11.4 ± 7.0 (4) μL/cm/hr. On coperfusion with intraluminal 1 uM cromakalim, STa reduced fluid absorption significantly (P<.02) to 24.7 ± 8.0 (10) μL/cm/hr, no different from STa challenge in the absence of cromakalim. Infusion i.v. with these agents also failed to restore fluid absorption after STa challenge. These observations do not support the proposed potassium ion permeability event as a necessary corollary of enterotoxin-mediated secretion. This makes it unlikely that modulators of such permeability prevent enterocyte secretion in diarrhoeal disease.